Immunocytochemistry of p16INK4a in liquid-based cervicovaginal specimens with modified Papanicolaou counterstaining. Issue 8 (7th February 2006) - Negri, G; Moretto, G; Menia, E; Vittadello, F; Kasal, A; Mian, C; Egarter-Vigl, E
Abstract : Aim: To evaluate the feasibility and value of a modified Papanicolaou counterstain for p16 INK4a immunostaining in liquid-based cervicovaginal samples. Methods: Immunocytochemical analyses were carried out with p16 INK4a and modified Papanicolaou counterstain on 81 liquid-based samples, including 23 of within normal limits (WNL), 6 of low-grade squamous intraepithelial lesion (LSIL), 20 of high-grade squamous intraepithelial lesion (HSIL), 16 of atypical squamous cells of undetermined significance (ASC-US) and 16 of atypical squamous cells, high-grade lesion cannot be excluded (ASC-H). Results were compared with histological or cytological follow-up. For comparison, samples from 29 more cases (10 of LSIL, 10 of ASC-H and 9 of HSIL) were immunostained with p16 INK4a and conventionally counterstained with haematoxylin. The intensity of immunostaining in cases of squamous intraepithelial lesion (SIL) was assessed using a 0–3 scoring system. Interobserver agreement was calculated by κ statistics. Results: Expression of p16 INK4a was detected in 3 of 23 cases of WNL, 4 of 6 cases of LSIL, all cases of HSIL, 5 of 16 cases of ASC-US and 13 of 16 cases of ASC-H. Excluding two cases with no residual dysplastic cells in the immunocytochemistry, all cases of cervical intraepithelial neoplasia (CIN)2 or CIN3 at follow-up expressed p16 INK4a and none of the p16 INK4a -negative cases showed a high-grade lesion at follow-up. No evident differences in pattern or intensity of p16 INK4a expression were observed between the specimens of the study and control groups. Interobserver agreement was significantly better in the study group than in the group with conventional immunostaining (combined κ 0.773 v 0.549; p<0.05), and still better, albeit statistically not significant, than with conventional immunostaining and cervical smear test together (combined κ 0.773 v 0.642). Conclusion: Immunocytochemistry with p16 INK4a and modified Papanicolaou counterstain may add to the cervicovaginal cytology the full potentiality of p16 INK4a without the need of a further slide and the risk of loss of dysplastic cells, yet maintaining the typical morphological features of the smear test.